Photoswitchable Micro-Supercapacitor Based on a Diarylethene-Graphene Composite Film - Liu, Zhaoyang; Wang, Hai I.; Narita, Akimitsu; Chen, Qiang; Mics, Zoltan; Turchinovich, Dmitry; Klaeui, Mathias; Bonn, Mischa; Muellen, Klaus (Journal of the American Chemical Society, 2017)
Stimuli-responsive micro-supercapacitors (MSCs) controlled by external stimuli can enable a wide range of applications for future on-chip energy storage. Here, we report on a photoswitchable MSC based on a diarylethene-graphene composite film. The microdevice delivers an outstanding and reversible capacitance modulation of up to 20%, demonstrating a prototype photoswitchable MSC. Terahertz spectroscopy indicates that the photoswitching of the capacitance is enabled by the reversible tuning of interfacial charge injection into diarylethene molecular orbitals, as a consequence of charge transfer at the diarylethene-graphene interface upon light modulation.
CRIS-Team Scopus Importer:2023-03-27